POLA KERJA DAN KONTRIBUSI PENDAPATAN WANITA PENGRAJIN TENUN SONGKET KHAS MELAYU RIAU DI KELURAHAN TIRTA SIAK KECAMATAN PAYUNG SEKAKI KOTA PEKANBARU - Kharisma W, Angelia; Kadarisman, Yoskar (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
This study is conducted in Tirta Siak District, the Sub-district of Pekanbaru Township. The purpose of this research is to know the level of the work pattern and the income contribution of housewives' activities as a traditional Malay Riau loom. The pattern of work is an everyday work system. Each individual has different patterns of work. In the study to see work pattern levels, there are indicators that a craftsman sets up, namely, working hours, working days, long hours and working productivity. In addition, contributions constitute a contribution of financial support to help the family economy. In this case the pattern of work determines much of the income that artisans earn. This kind of research is a quantitative approach to research. The need for data, including primary data obtained through recharging questionnaires and secondary data. The population count was 20 craftsmen. The sample technique used is the saturated sample means the entire population is treated as a sample that's 20 people. Research results show that the level of the work pattern of songket weaving affairs is categorized medium by an average score of 8. The highest contributions for loom workers about 84.2% or Rp 2,400,000 and the lowest contributions is about 4.8% or Rp 250,000. From the overall contributions, an average of 30.0% is obtained, which is categorized as a moderate level of contribution. It can be concluded that the pattern of work done by craftsmen has a relationship to with the contribution of respondents income to the family economy. . Keywords: Work pattern, housewives' activities as craftsmen